OUTCOMES OF LAPAROSCOPIC NISSEN FUNDOPLICATION FOR THE TREATMENT OF GASTROESOPHAGEAL REFLUX DISEASE - Tran, Manh Doan; Lai, Van Nong; La, Van Phu (Cantho Journal of Medicine and Pharmacy, 2025)
Background: Gastroesophageal reflux disease (GERD) is a common condition that significantly impacts patients' quality of life. While medical therapy, particularly proton pump inhibitors, remains the first-line treatment, a considerable number of cases fail to achieve symptom relief. For these patients, laparoscopic Nissen fundoplication has long been recognized as the gold standard surgical intervention. This study aims to evaluate the safety and efficacy of laparoscopic Nissen fundoplication in the management of GERD. Objectives: To assess the treatment outcomes of laparoscopic Nissen fundoplication in GERD patients at Can Tho General Hospital from 2023 to 2025. Materials and methods: This is an interventional clinical study without a control group, conducted on 34 patients diagnosed with GERD between January 2023 and April 2025. Patient selection was based on failure to respond to medical therapy and confirmation of GERD through clinical assessment and diagnostic tests. Results: The mean age of patients included in the study was 34.71 ± 8.93 years. Among them, 23 patients (67.6%) were male, and 11 patients (32.4%) were female. The average GERD-Q score was 14.26 ± 1.69. Intraoperative findings showed that 26 patients (76.5%) had a type I hiatal hernia. The mean operative time was recorded at 124.56 ± 27.37 minutes. Postoperative outcomes were favorable, with 32 patients (94.1%) achieving good results and 2 patients (5.9%) classified as fair outcomes. Conclusion: Laparoscopic Nissen fundoplication has proven to be a safe and effective treatment option for GERD patients who do not respond to medical therapy. The procedure demonstrates high success rates with minimal complications, reinforcing its role as the preferred surgical intervention for refractory GERD cases.